KOMPETENSI KEPRIBADIAN GURU SEBAGAI FAKTOR KUNCI DALAM PEMBENTUKAN KARAKTER PESETA DIDIK: STUDI LITERATUR - Reynanda Tablita Putri; Arzahwa Putri Asoka; Achmad Muhtadin; Ikmawati (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
Teacher personality competence is an essential component in education that plays a significant role in shaping students’ character. Amid the challenges of modernization and technological advancement, character development has become increasingly complex and requires teachers to serve as role models. This article aims to examine the role of teacher personality competence as a key factor in shaping students’ character through a literature review approach. This study employed a qualitative approach using a literature review method. Secondary data were collected from 10 accredited national journal articles (SINTA 1–6) published within the last five years (2021–2026) through Google Scholar and the SINTA Portal. Data were analyzed using content analysis, including identification, selection, descriptive presentation, and synthesis of findings. The results indicate that teacher personality competence supports character internalization through exemplary behavior, emotional stability, and adaptability to changing times. These findings confirm that teachers’ personality significantly influences students’ academic development and integrity in face-to-face and online learning. Therefore, strengthening teacher personality competence should be prioritized in professional development policies to improve character education sustainably.